2019
DOI: 10.1021/acsami.9b16325
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Indium Filament Revolution in Transparent Bipolar ITO/SiOx/ITO Resistive Switching Memories

Abstract: Transparent resistive switching random access memory (ReRAM) is of interest for the future integrated invisible circuitry. However, poor understanding of its working mechanism in transparent ReRAMs with the indium tin oxide (ITO) electrode is still a critical problem and will hinder its widespread applications. To reveal the actual working mechanism in transparent ReRAMs with the ITO electrode, we investigate the transparent ITO/SiO x /ITO memory devices (∼82% transmittance in the visible region) and compare i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…In these RRAMs with an ITO electrode, different switching mechanisms such as composition modulation, electron trapping/detrapping, and oxygen ion migration were reported, ,,, which did not involve the ITO electrode. In our previous work (i.e., ITO/hBN/graphene and ITO/SiO x /Au RRAMs), , the indium (In) filaments were found to be responsible for the bipolar resistive switching behaviors, indicating that the ITO electrode can generate conductive filaments due to the In–O bond break and indium diffusion under an electric field. However, the memory devices’ behaviors and switching mechanisms are always uncertain due to their different electrical operations, different structures, and different material systems .…”
Section: Introductionmentioning
confidence: 97%
“…In these RRAMs with an ITO electrode, different switching mechanisms such as composition modulation, electron trapping/detrapping, and oxygen ion migration were reported, ,,, which did not involve the ITO electrode. In our previous work (i.e., ITO/hBN/graphene and ITO/SiO x /Au RRAMs), , the indium (In) filaments were found to be responsible for the bipolar resistive switching behaviors, indicating that the ITO electrode can generate conductive filaments due to the In–O bond break and indium diffusion under an electric field. However, the memory devices’ behaviors and switching mechanisms are always uncertain due to their different electrical operations, different structures, and different material systems .…”
Section: Introductionmentioning
confidence: 97%
“…24(c) and (d). Also, Qian et al [242] elaborates a transmittance of ∼ 82% at ∼ 600 nm obtained in ITO/SiO x /ITO as shown in Fig. 24(e) and (f).…”
Section: F Transparent/flexible Zno Based Rrammentioning
confidence: 76%
“…Fabrication parameters strongly regulate the growth and conduction properties of TCO [254], [255]. Nevertheless, some studies have shown that the modification and manipulation of the TCO electrodes may trigger the oxygen vacancy concentration, thus, enhancing the device performance [242], [256], [257]. Various methods were proposed to deposit ZnO switching layer on TCO electrodes, like the solution-processed (sol-gel) method [167], [189], [246], [258]- [260], high-power pulse laser deposition (PLD) [238], [261]- [263], atomic layer deposition (ALD) [264], thermal-roll lamination technique [265], hydrothermal growth [266], RF magnetron sputtering [53], [151], [202], [205], [267]- [270], metal-organic chemical vapor deposition [271]- [273].…”
Section: F Transparent/flexible Zno Based Rrammentioning
confidence: 99%
“…Electrodes in conventional electronic devices are usually used to transport paths for carriers as an auxiliary role, however, they significantly influence the switching behaviors in memristor devices. [ 2 ] On the one hand, the common electrode materials can be classified into five categories based on composition, including simple substance electrodes (most metals), alloy electrodes (e.g., Cu–Te, [ 12 ] Ag–Cu [ 13 ] ), silicon‐based electrodes (e.g., n‐Si, [ 14 ] p‐Si [ 15 ] ), nitride‐based electrodes (e.g., TiN, [ 16 ] TaN [ 17 ] ) and oxide‐based electrodes (e.g., ITO, [ 18 ] Nb‐doped SrTiO 3 [ 19 ] ). On the other hand, the common electrodes can be sorted into four types based on their functions in switching behaviors, including inert electrodes (IE, e.g., Pd, [ 20 ] Pt, [ 21 ] Ir [ 22 ] ) which has almost no effect on switching, relatively active electrodes (e.g., Ti, [ 23 ] W, [ 24 ] Ta [ 25 ] ) which is helpful for the formation of vacancy‐based CFs, active electrodes (AE, e.g., Ag, [ 26 ] Cu [ 27 ] ) which can act as the source of metallic CFs, and other electrodes for specific purposes (e.g., ITO, [ 28 ] FTO, [ 29 ] PEDOT:PSS [ 30 ] ).…”
Section: Electrodesmentioning
confidence: 99%